Pengembangan Lembar Kerja Peserta Didik Berbasis Problem Based Learning-Flipped Classroom untuk Meningkatkan Kemampuan Transformasi Pengetahuan : The Development of Students’ Problem Based Learning-Flipped Classroom Worksheets to Improve Knowledge Transformation Ability - Dewi Ningsih; Muhammad Rusdi; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2018)
Most of the eleventh-grade students of SMAN 3 Jambi City find difficulties in understanding the concepts of Coordination Systems in Biology subject. This study aims to create a learning tools in the form of students’ worksheets based on problem-based learning-flipped classroom. This study employs ADDIE Model. Validations were undertaken by learning design, material, and product design experts. Where as, best practice validation was done by a Biology teacher teaching in SMAN 3 Jambi City. Research subject was students of SMAN 3 consisting of 3 students for individual trial and 9 students for small group trial. Data from validation results were described qualitatively. The design stage produces a worksheet prototype based on problem-based learning-flipped classroom. The development stage produces a new version of student worksheet that has been positively responded by the research participants. In implementation stage, the worksheet has been considered very good by students. In evaluation stage, the study has produced a sudent worksheet that accommodates students needs to improve their ability in transforming knowledge. Based all stages of the ADDIE, it can be concluded that the produced student worksheet is interesting, easy to use and easy to understand. It helps students to learn coordination systems more effectively. The created student worksheet can be further developped into an e-student worksheet.